Correlation of changes in hemodynamic response as measured by cerebral optical spectrometry with subjective pain ratings in volunteers and patients: a prospective cohort study - Eisenried, Andreas; Austin, Naola; Cobb, Benjamin; Akhbardeh, Alireza; Carvalho, Brendan; Yeomans, David C.; Tzabazis, Alexander Z. (Journal of Pain Research, 2018)
Purpose: Noninvasive cerebral optical spectrometry is a promising candidate technology for the objective assessment physiological changes during pain perception. This study's primary objective was to test if there was a significant correlation between the changes in physiological parameters as measured by a cerebral optical spectrometry-based algorithm (real-time objective pain assessment [ROPA]) and subjective pain ratings obtained from volunteers and laboring women. Secondary aims were performance assessment using linear regression and receiver operating curve (ROC) analysis. Patients and methods: Prospective cohort study performed in Human Pain Laboratory and Labor and Delivery Unit. After institutional review board approval, we evaluated ROPA in volunteers undergoing the cold pressor test and in laboring women before and after epidural or combined spinal epidural placement. Linear regression was performed to measure correlations. ROCs and corresponding areas under the ROCs (AUC), as well as Youden's indices, as a measure of diagnostic effectiveness, were calculated. Results: Correlations between numeric rating scale or visual analog scale and ROPA were significant for both volunteers and laboring women. AUCs for both volunteers and laboring women with numeric rating scale and visual analog scale subjective pain ratings as ground truth revealed at least good (AUC: 70%-79%) to excellent (AUC >90%) distinction between clinically meaningful pain severity differentiations (no/mild-moderate-severe). Conclusion: Cerebral Optical Spectrometry-based ROPA significantly correlated with subjectively reported pain in volunteers and laboring women, and could be a useful monitor for clinical circumstances where direct assessment is not available, or to complement patient-reported pain scores.
EVALuna2:36284